Family C G-Protein-Coupled Receptors in Alzheimer’s Disease and Therapeutic Implications - Dal Prà, Ilaria; Armato, Ubaldo; Chiarini, Anna (Frontiers in Pharmacology, 2019)
Alzheimer's disease (AD), particularly its sporadic or late-onset form (SAD/LOAD), is the most prevalent (96-98% of cases) neurodegenerative dementia in aged people. AD’s neuropathology hallmarks are the intra-brain accumulation of amyloid-beta peptides (Abetas) and of hyperphosphorylated Tau (p-Tau) proteins, diffuse neuroinflammation, and progressive death of neurons and oligodendrocytes. Mounting lines of evidence suggest that Family C G-protein-coupled receptors (GPCRs), which include gamma-aminobutyric acid B (GABAB), metabotropic glutamate (mGlu1-8) receptors, and the calcium-sensing receptor (CaSR), are involved in many neurotransmitter systems that dysfunction in AD. This review updates the available knowledge about the roles of GPCRs, particularly those expressed by brain astrocytes, in SAD/LOAD onset and progression, taking stock of their respective mechanisms of action and of their potential as anti-AD therapeutic targets. In brief, GABABRs prevent Abetas synthesis and neuronal hyperexcitability; Group I mGluRs play important pathogenetic roles in transgenic AD-model animals; and when bound to Abetas, CaSRs of human cortical astrocytes and neurons crucially promote further synthesis and release of Abetas surpluses and of hyperphosphorylated Tau proteins, NO, VEGFA, and proinflammatory agents; concurrently Abetas•CaSR signaling hinders the release of the neurotrophic, GABABR1a agonist soluble APP-α peptide--effects that altogether progressively kill human cortical neurons. Several negative allosteric modulators (NAMs) of the CaSR suppress all these noxious effects of Abetas•CaSR signaling in human cortical astrocytes and neurons thus safeguarding neurons’ viability in vitro and hence raising hopes about their potential therapeutic benefits in AD patients. Further basic and clinical investigations on these hot topics are needed also taking heed that activation of brain Family C GPCRs may elicit divergent upshots according to the models studied.